Recursos didácticos físicos en la enseñanza y aprendizaje de Ciencias Naturales para quinto grado, escuela EGB Rosa Josefina Burneo de Burneo 2023-2024 - Ruiz Pinta, Gabriela Julissa (2024)
The present research is focused on analysing the impact of physical teaching resources on the teaching of Natural Sciences for fifth grade students at Escuela Rosa Josefina Burneo during the period 2023-2024. The general objective was to determine how these resources influence the teaching and learning process. The specific objectives included diagnosing the use of physical teaching resources, applying these resources to improve teaching and learning, and evaluating their contribution in the area of Natural Sciences. The research adopted a mixed approach, combining descriptive features and a quasi-experimental design. The methods used were: scientific, descriptive, analytical, synthetic, inductive, deductive, statistical and hermeneutic. The sample included sixteen students and one teacher, assessed by means of a structured teacher interview and a student survey based on curriculum content and teaching materials. The results revealed that all students needed to improve their learning processes, which motivated the implementation of the proposal ‘Innovative Creative Little Hands’, based on physical didactic resources such as a model, pyramid, puzzle and spinner. These resources proved to be an effective strategy to improve the educational process, highlighting the active individual and group participation of the students, as well as the motivation and in the activities implemented to share knowledge in the classroom. Not only did they facilitate a deep and practical understanding of Natural Science concepts, but they also awakened students' motivation, curiosity and creativity, making learning a more active, experiential and practical process.